2020
DOI: 10.3390/w12092457
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Pumped Hydro Storage Energy Solutions towards Wind and PV Integration: Improvement on Flexibility, Reliability and Energy Costs

Abstract: This study presents a technique based on a multi-criteria evaluation, for a sustainable technical solution based on renewable sources integration. It explores the combined production of hydro, solar and wind, for the best challenge of energy storage flexibility, reliability and sustainability. Mathematical simulations of hybrid solutions are developed together with different operating principles and restrictions. An electrical generating system composed primarily by wind and solar technologies, with pumped-sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 38 publications
(44 reference statements)
0
13
0
Order By: Relevance
“…Moreover, head losses due to pipes and fittings are also shown in Figure 5B that accounts for 3.9% of the served energy (see Figure 3A). The PHS models used in literature studies for feasibility and techno-economic optimization often overlooked them that may undermine the optimal sizing of RES (Makhdoomi and Askarzadeh, 2020;Simã o and Ramos, 2020;Al-Ghussain et al, 2020;Bhayo et al, 2020).…”
Section: Energy and Cost Balance For Off-grid Renewable Energy Systemmentioning
confidence: 99%
“…Moreover, head losses due to pipes and fittings are also shown in Figure 5B that accounts for 3.9% of the served energy (see Figure 3A). The PHS models used in literature studies for feasibility and techno-economic optimization often overlooked them that may undermine the optimal sizing of RES (Makhdoomi and Askarzadeh, 2020;Simã o and Ramos, 2020;Al-Ghussain et al, 2020;Bhayo et al, 2020).…”
Section: Energy and Cost Balance For Off-grid Renewable Energy Systemmentioning
confidence: 99%
“…The solar PV electricity output's estimation was based on a model established by the National Renewable Energy Laboratory (NREL) [36] using the formula in Equation (4).…”
Section: Objective Functionmentioning
confidence: 99%
“…Some studies proposed PHS-PV-wind systems as a way to increase solar energy penetration [19,21] particularly for small and isolated power systems in remote areas leading to an increase in capacity of 40% of the maximum wind penetration level during peak hours [21]. Simão and Ramos [36] investigated the combined generation of hydro, solar, and wind for the best challenge of energy storage flexibility, reliability, and sustainability. They found that the combined production showcased that technically the pumped hydro storage with wind and PV was the best solution to realize energy autonomy and improve its flexibility and dependability.…”
Section: Introductionmentioning
confidence: 99%
“…The result of a publication on electricity costs in India shows that MPS systems can be economically viable [17]. In contrast, other publications concerned with modelling small hydropower plants [18][19][20][21][22][23] in combination with photovoltaic (PV) systems [24], wind turbines [25], or both [26], leave open the question of how such a system can be operated economically.…”
Section: Introductionmentioning
confidence: 99%